1996
DOI: 10.1016/s0006-3495(96)79386-4
|View full text |Cite
|
Sign up to set email alerts
|

Reversible adsorption and nonreversible insertion of Escherichia coli alpha-hemolysin into lipid bilayers

Abstract: Alpha-Hemolysin is an extracellular protein toxin (107 kDa) produced by some pathogenic strains of Escherichia coli. Although stable in aqueous medium, it can bind to lipid bilayers and produce membrane disruption in model and cell membranes. Previous studies had shown that toxin binding to the bilayer did not always lead to membrane lysis. In this paper, we find that alpha-hemolysin may bind the membranes in at least two ways, a reversible adsorption and an irreversible insertion. Reversibility is detected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
42
1
16

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 44 publications
(62 reference statements)
5
42
1
16
Order By: Relevance
“…The RTX toxins are known to be secreted into the aqueous solution but also to be membrane-interacting proteins (11). Neither the water-soluble nor the membrane-embedded structures of these toxins (and LtxA in particular) have been solved; however, it has been proposed that this family of toxins undergoes a conformational change upon membrane association (12).…”
mentioning
confidence: 99%
“…The RTX toxins are known to be secreted into the aqueous solution but also to be membrane-interacting proteins (11). Neither the water-soluble nor the membrane-embedded structures of these toxins (and LtxA in particular) have been solved; however, it has been proposed that this family of toxins undergoes a conformational change upon membrane association (12).…”
mentioning
confidence: 99%
“…HlyA interaction with the target membrane is a complex process, of which many aspects are still poorly understood. The process includes two main steps, namely reversible binding (adsorption) and irreversible insertion (7). Binding occurs probably via specific receptors (8 -10), although the latter are not essential, since the toxin has also a lytic effect, at higher concentrations, on pure lipid liposomes (9).…”
mentioning
confidence: 99%
“…However, only when the protein had been preincubated with this cation did the lytic effect follow toxin binding. In a further study, Bakás et al (66) applied to α-hemolysin a procedure developed by Tomita et al (67) that allowed the distinction between reversibly and irreversibly bound HlyA (Figure 4). The method consists essentially of incubating liposomes in the presence of toxin, then washing to remove the non-bound protein.…”
Section: Reversible Adsorption and Nonreversible Insertion Of Hlya Inmentioning
confidence: 99%
“…Using this procedure, Bakás et al (66) were able to show that α-hemolysin may bind the membranes in at least two ways, a reversible adsorption and an irreversible insertion. Comparison of irreversible binding and cell lysis results demonstrated that not even irreversible insertion leads necessarily to membrane damage.…”
Section: Reversible Adsorption and Nonreversible Insertion Of Hlya Inmentioning
confidence: 99%
See 1 more Smart Citation